Spectrophotometric Studies on the Reaction of Diaveridine with Some Sulfonphthalein Dyes Based on Ion-Pair/Ion-Associate Complexes Formation - A. L. El-Ansary; N. S. Abdel-Kader; A. M. Asran (Journal of Spectroscopy)
The ion-associate complexes of diaveridine were prepared in a solution and studied spectrophotometrically. The bulky counter anions such as sulfonphthalein acidic dyes, namely, bromocresol green (I), bromophenol blue (II), bromothymol blue (III), bromocresol purple (IV), bromocresol blue (V), o-cresol red (VI), p-cresol blue (VII), and m-cresol purple (VIII) were used for ion-associate complexes formation. The optimal characteristics for the color formation and the stoichiometry of the reaction were evaluated. Spectral characteristics and stability constants of the formed ion associates are discussed in terms of nature of donor and acceptor molecular structures. The molar absorptivities and association constants for the colored complexes were evaluated using the Benesi-Hildbrand equation. Conformity to Beer’s law enabled the assay of dosage form of the drug. The molar absorptivity, specific absorptivity, Sandell sensitivity, correlation coefficient, and detection and quantification limits were also calculated. The methods were validated in terms of accuracy, specificity, precision, and linearity. Also, spectrophotometric determination of the drug in pure and pharmaceutical preparations was tested.